The Need for Special Education Among ELBW and SGA Preterm Children: A Cohort Study - van Beek, Pauline E.; van de Par, Kaylee; van der Horst, Iris E.; van Baar, Anneloes L.; Vugs, Brigitte; Andriessen, Peter (Frontiers in Pediatrics, 2021)
Background: Preterm infants with pre- or postnatal growth restriction may have an additional risk of adverse neurodevelopmental outcome. Whereas reduced cognitive ability and behavioural problems have consistently been associated with prematurity, a more comprehensive evaluation is necessary to identify those preterm infants who are at increased risk for difficulties in school performance. This study evaluated the association between extremely low birth weight (ELBW) and the need for special education, and determined if there is an additional risk for the need for special education among SGA children. Methods: Single-centre cohort study including singleton children born below 30 weeks’ gestation between 1990 and 2011 and followed into 2019. ELBW+ was defined as a birth weight below 1000g, which was compared to ELBW-. Within all ELBW+ children, SGA+ was defined as a birth weight <10th percentile according to Fenton, which was compared to SGA-. The dichotomous outcome measurement was the need for special education at 8 years of age or not, reflecting if the children required a special educational setting designed to accommodate educational, behavioural, and/or medical needs. Results: In total, 609 children were eligible for follow-up, of whom 390 (64%) children were assessed at eight years. Of these, 56 (14%) children needed special education, most often determined by cognitive deficiency (43%), behavioural problems (29%) or both (16%). Among the 191 ELBW+ children, 35 (18%) attended special education, compared to 21 (11%) among ELBW- children (p-value 0.041). A decreasing risk for the need for special education was found from 25% in ELBW+/SGA+ children to 16% in ELBW+/SGA- children and 11% in ELBW-/SGA- children (p-value 0.025). Multivariable logistic regression showed an odds ratio of 2.88 (95%CI 1.20-6.78) for ELBW+/SGA+ children versus ELBW-/SGA- children for the need for special education. Conclusions: This study showed that ELBW children are at increased risk for the need for special education compared to non-ELBW children. In addition, children that are both ELBW and SGA do have the highest risk for the need for special education. Classifying children as ELBW and SGA can be useful in follow-up for identifying preterm children with an additional risk for adverse long-term outcome.